Histomorphometric and sympathetic innervation of the human superficial temporal artery - Sreenivasulu Reddy; Pramod Kumar; Keerthana Prasad (Indian Journal of Plastic Surgery)
Context: Following microvascular surgeries, stenosis and spasm of the arterial graft or the recipient vessel are serious complications which are often caused by intimal hyperplasia and perivascular nerves, respectively. Aims: The purpose of this study was to understand the characteristics of arterial wall and sympathetic innervation of the human superficial temporal artery (STA) and also, the effect of aging on STA. Methods and Materials: Fifty-two fresh human STA (frontal branch) samples were obtained from 26 cadavers (19 males and 7 females) between the ages of 19 and 83 years. Samples were divided into three age groups: G1, 19-40 years; G2, 41-60 years; G3, over 61 years. 5μm-thin sections of each sample were taken and stained with haematoxylin-eosin, Verhoff's and tyrosine hydroxylase (TH) immunostaining. Results: The well-defined internal elastic lamina (IEL) was observed in all samples of STA, whereas external elastic lamina (EEL) was not prominent in almost all cases or absent in few cases. This might be the important factor in the process of intimal and medial hyperplasia in the frontal branch of STA. Notably, intimal thickening appeared from second decade of life. Sympathetic fibres are located mainly in tunica adventitia and outer media. Mean adventitial and sympathetic areas were found to be 0.080 and 0.010mm2, respectively. Statistical analysis used: One-way ANOVA followed by Tukey HSD post hoc test by using the SPSS 11.5 software. Conclusions: STA is prone to age related pathological changes. Sympathetic index may be used for analysis of sympathetic fibre-related problems (vasospasm, migraine) of the STA.